Assessment of cervicovaginal smear and HPV DNA co-test for cervical cancer screening: implications for diagnosis and follow-up strategies - Shaheen, Nazma; Afrin, Syeda Sadia; Ripon, Mohammad Rezaul Karim; Nahar, Kamrun; Khan, Abu Anis; Haque, Sharmin (International Journal of Research in Medical Sciences, 2024)
Background: Cancer of the cervix, despite being a preventable disease, continues to be a significant public health problem in females. In recent years, much new development has taken place in the field of screening, diagnosis and management of cervical intraepithelial neoplasia. Methods: A total of 980 patients aged between 20 to 60 years were included in the study. All the patients have gone through Pap test, RT-PCR for HPV test and colposcopy biopsy. Then the sensitivity and specificity are calculated. Retrospectively selected Pap specimens with RT-PCR HPV testing results obtained from the Department of Pathology of Sheikh Fozilatunnessa Mujib Memorial KPJ Specialized Hospital, Gazipur, Bangladesh from July 2022 to July 2024 followed by the result is correlated with Colposcopy guided biopsy. Results: We found 250 cases of human papilloma virus RT-PCR positive, 433 cases of Pap test positive result and 399 cases of positive colposcopy biopsy result. So, The HPV test was demonstrated to be more sensitive (75%) than specific (55%) and was more sensitive than colposcopy for detecting CIN changes (75% vs. 73%). Conclusion: HPV tests showed a higher sensitivity than colposcopy, but colposcopy results presented higher specificity. Combining HPV testing and colposcopy proved to be the most efficient method for detecting CIN lesions.